Kajian Tanaman Hiperakumulator Pada Teknik Remediasi Lahan Tercemar Logam Berat - Ni Luh Widyasari (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
Increased activity in the industrial sector can increase the production of solid, liquid and gas waste. Industrial waste that is indicated by heavy metals can reduce environmental quality. Heavy metal pollution can occur in soil and waters which will disturb the ecosystem in it. Heavy metals not only have a negative impact on the environment but also on the health of the human body. There have been many chemical and physical techniques for dealing with heavy metals, but they are still not effective because these techniques are considered to increase the level of pollution and require a large amount of money. Therefore, the remediation technique using hyperaccumulator plants is one of the solutions in efforts to resolve heavy metals polluted in a soil and waters. Vetiveria zizanioides, Sansevieria trifasciata, Eichhornia crassipes are hyperaccumulator plants of capable absorbing and accumulating heavy metals by phytoextraction, phytodegradation and rhizofiltration mechanism.